An exponential stabilization of random impulsive control systems and its application to chaotic systems. (2nd September 2022) - Vinodkumar, A.; Senthilkumar, T.; Işık, Hüseyin; Hariharan, S.; Gunasekaran, Nallappan
Abstract : This paper addresses the problem of pth moment exponential stability and stabilization for random impulsive control systems. Some novel pth moment exponential stability and synchronization approaches are established based on the method of maximum and minimum eigenvalues by using the Lyapunov functions and Razumukhin technique. Finally, we show that the stability and synchronization behavior of random impulses are faster than the fixed time impulses. Some physical examples are given to verify the validity and usefulness of the results obtained.